The economic resilience of the Austrian agriculture since the EU accession - Erika Quendler; Mangirdas Morkūnas (Journal of Risk and Financial Management, 2020)
Ensuring sustainable and economically viable agriculture requires economic resilience before, throughout, and after a shock. This paper studies the economic resilience of Austrian agriculture within the period of 1995 to 2019. However, methods for tracking changes in economic resilience have so far seen only limited application in agriculture. The index for the analysis and measurement of economic resilience is based on four areas: financial flexibility, stability in following the development path, diversification of activities, and diversification of export markets. As results show, Austrian agriculture is of interest because of the very high level of economic resilience, ranging from 0.83 to 0.92 in the period researched, thereby displaying a high capacity to absorb shocks. Generally, these results indicate that Austrian agriculture is forgiving of shocks and thus very economically resilient. These results provide context for developing generalizations on economic resilience in agriculture and its fundamental function for producing effective food security within a sustainable transition path. Some concluding suggestions propose possible future areas of research.
Keywords: 330; agricultural sector; Austria; economic resilience; index